Dynamic Progress in Technological Advances to Study Lipids in Aging: Challenges and Future Directions - Gao, Fangyuan; Tom, Emily; Skowronska-Krawczyk, Dorota (Frontiers in Aging, 2022)
Lipids participate in all cellular processes. Diverse methods have been developed to investigate lipid composition and distribution in biological samples to understand the effect of lipids across an organism’s lifespan. Here, we summarize the advanced techniques for studying lipids, including mass spectrometry-based lipidomics, lipid imaging, chemical-based lipid analysis and lipid engineering and their advantages. We further discuss the limitation of the current methods to gain an in-depth knowledge of the role of lipids in aging, and the possibility of lipid-based therapy in aging-related diseases.